Review of Smog Chamber Experiments for Secondary Organic Aerosol Formation - Kim, Hyun; Kang, Dahyun; Jung, Heon Young; Jeon, Jongho; Lee, Jae Young (Atmosphere, 2024)
In this study, we reviewed smog chamber systems and methodologies used in secondary organic aerosol (SOA) formation studies. Many important chambers across the world have been reviewed, including 18 American, 24 European, and 8 Asian chambers. The characteristics of the chambers (location, reactor size, wall materials, and light sources), measurement systems (popular equipment and working principles), and methodologies (SOA yield calculation and wall-loss correction) are summarized. This review discussed key experimental parameters such as surface-to-volume ratio (S/V), temperature, relative humidity, light intensity, and wall effect that influence the results of the experiment, and how the methodologies have evolved for more accurate simulation of atmospheric processes. In addition, this review identifies the sources of uncertainties in finding SOA yields that are originated from experimental systems and methodologies used in previous studies. The intensity of the installed artificial lights (photolysis rate of NO2 varied from 0.1/min to 0.40/min), SOA density assumption (varied from 1 g/cm3 to 1.45 g/cm3), wall-loss management, and background contaminants were identified as important sources of uncertainty. The methodologies developed in previous studies to minimize those uncertainties are also discussed.
Keywords: Chamber experiments; Chamber system; Emission; Measurement system; Organic aerosol; Organic aerosol formation; Secondary organic aerosol; Smog chambers; Sources of uncertainty; Wall loss; emission; measurement system; secondary organic aerosol; smog chamber; wall loss